Case Report: A rare case of recurrent ascites after anti-Claudin18.2 antibody therapy for metastatic gastric cancer while responding sustainingly - Liu, Jinlu; Jiang, Dan; Lei, Qingqiang; Zhu, Qing; Zhu, Hong (Frontiers in Oncology, 2023)
Background Gastric cancer remains one of the deadliest malignancies in the world, thus urgently requiring effective and safe therapeutics. Claudin18.2 is a member of the tight junction protein family specifically expressed in gastric cancer cells. Monoclonal antibodies targeting Claudin18.2 have been receiving increasing attention recently. ASKB589 is a humanized monoclonal antibody targeting Claudin18.2. Case presentation This case described a 65-year-old Chinese man diagnosed with gastric cancer metastasizing to the liver and multiple lymph nodes. The biomarker examination revealed that he had proficient mismatch repair (pMMR), human epidermal growth factor receptor 2 (HER2) was negative, and the combined proportion score (CPS) of PD-L1 (22C3) was 1. After being proven to be moderately positive for Claudin18.2 expression, he received ASKB589 and CAPOX (oxaliplatin and capecitabine) chemotherapy. After a six-cycle therapy (from 14 July 2022 to 29 November 2022), the target tumor was evaluated for partial response (PR) by the investigator based on the enhanced CT scan according to the Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 criteria. However, this patient also suffered from intolerable ascites that gradually aggravated during the therapy, which was not controlled well by the supporting therapy. Therefore, the patient stopped receiving the combined therapy in our hospital and did not receive any other anti-tumor treatment. After 4 months of discontinuation of the drug, the patient’s ascites almost disappeared, while the tumor continued to reduce and almost achieved clinically complete relapse (cCR). His progression-free survival (PFS) reached at least 10 months. Conclusion This is the first case of severe ascites reported after anti-Claudin18.2 monoclonal antibody treatment for advanced gastric cancer. At the same time, the patient still benefited significantly from this incomplete treatment even after discontinuation of the drug and the PFS reached at least 10 months. The ascites might be an immune adverse effect related to the monoclonal antibody-induced antibody-dependent cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). Further mechanisms remain to be investigated.